In vivo studies on detoxifying actions of aqueous bark extract of Prosopis cineraria against crude venom from Indian cobra (Naja naja) - Thirunavukkarasu Sivaraman; Sivarathri Siva Rajesh; Veerayan Elango (Bangladesh Pharmacological Society, 2013)
Detoxification effect of aqueous, methanol and petroleum ether extracts of medicinal plants such as Aristolochia bracteolata, Mucuna pruriens, Prosopis cineraria and Rauvolfia tetraphylla was systematically screened against lethality of crude venom of Naja naja using Swiss albino mice as animal models. We have herein demonstrated that aqueous bark extract of P. cineraria has substantial anti-venom potential vis-à-vis other extracts used in the present study. The aqueous extract at the dose of 14 mg/kg b.w. was able to almost completely neutralize the lethal activity of 3LD50 (1.12 mg/kg b.w.) of the cobra venom and the extract did not cause any types of adverse side-effects to the animal models. The investigation justifies not only the veraciousness of the extract used by traditional healers of Asian subcontinent as antidotes to snake venoms and also suggests that the aqueous extract should contain specific inhibitors to most principle toxic components of the crude venom.